2022
DOI: 10.3390/nano12193545
|View full text |Cite
|
Sign up to set email alerts
|

Green Route to Produce Silver Nanoparticles Using the Bioactive Flavonoid Quercetin as a Reducing Agent and Food Anti-Caking Agents as Stabilizers

Abstract: In previous work, the isolated polyphenolic compound (PPC) quercetin was used as a reducing agent in the formation of silver nanoparticles (AgNPs), testing two types of quercetin. This PPC is a bioactive molecule that provides the electrons for the reduction of silver ions to zerovalent silver. The results demonstrated that quercetin in dietary supplement presentation was better than reagent grade quercetin for the synthesis of AgNPs, and the difference between them was that the dietary supplement had microcry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The existing studies in the literature show that different plant extracts, microorganisms, or bee pollen were used for the green synthesis of silver nanoparticles [ 4 , 8 , 9 , 10 , 11 ]. Therefore, to confirm the presence of bioactive compounds, which, according to the literature [ 60 , 61 , 62 ], act as reducing agents, the TPC and TFC of the BB extracts were measured. LC/MS analysis was also performed to identify the existing individual polyphenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The existing studies in the literature show that different plant extracts, microorganisms, or bee pollen were used for the green synthesis of silver nanoparticles [ 4 , 8 , 9 , 10 , 11 ]. Therefore, to confirm the presence of bioactive compounds, which, according to the literature [ 60 , 61 , 62 ], act as reducing agents, the TPC and TFC of the BB extracts were measured. LC/MS analysis was also performed to identify the existing individual polyphenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The spectra show a characteristic peak at 422 nm that appeared from the first moment of contact and that increased in intensity as days went by. Other authors have identified similar peaks in this characteristic region of Ag-NPs, which is associated with the phenomenon known as surface plasmon resonance (SPR) [ 39 ] and causes non-absorbed light to be detected in the UV-vis spectrum. [ 40 ].…”
Section: Resultsmentioning
confidence: 97%